Arenga Palm Harvesting and Processing Practices by the Community of Kekait Village, West Lombok: Praktik Pemanenan dan Pengolahan Pohon Aren oleh Masyarakat Desa Kekait, Lombok Barat - Sawaka, Rizki Sukarman; Zahra, Adelia; Putri, Regina Natasya (Indonesian Journal of Tropical Biology, 2025)
This study aims to describe the traditional practice of harvesting and processing palm trees (Arenga pinnata) by the people of Kekait Village, West Lombok, as well as examining the cultural values and ethnobotanical knowledge that accompany them. The research method used is qualitative with an ethnobotanical approach, through participatory observation, in-depth interviews, and field documentation. The results of the study show that palm trees are still abundant and scattered on land owned by residents and wild land. The sap tapping technique is carried out through the stages of mantokin and bêgéyong, as well as the use of traditional tools such as bamboo, belakas, and laru wood as natural bioinhibitors. The process of processing sap into ant sugar is carried out without chemicals, reflecting local wisdom in maintaining the quality and sustainability of the environment. It was also found that human behavior and emotions can affect crop yields, which suggests an ecological-spiritual relationship between humans and trees. These findings confirm the importance of preserving local knowledge as part of biocultural conservation and sustainable management of natural resources.